J13 Prescription usage for treatment of irritability, perseverative behaviors, and chorea in huntington's disease. (16th November 2010) - van Duijn, E; Groves, M; Craufurd, D; Anderson, K; Guttman, M; Wexler, E; Perlman, S; Rosenblatt, A; van Kammen, D P; Giuliano, J; Burgunder, J-M; Goodman, N; et al.
Abstract : Background: Despite large gaps in evidence-based knowledge, clinical experience supports the use of pharmacologic treatments for many symptoms of Huntington's disease (HD). Aims: The project goal is to develop consensus guidelines based on expert clinical experience to improve quality of HD care. Methods: The survey was developed by 9 international experts, and designed as a highly iterative and systematic method of soliciting expert opinions on the pharmacologic treatment of irritability, perseverative behaviors, and chorea in HD. Fifty-five experts from Australia, Europe and North America responded to at least one of the surveys. Results: For irritability, SSRI was first choice of 58%, an antipsychotic was first choice for 22%, a mood stabilizing anticonvulsant 14%, and benzodiazepine 2%. For perseverative behaviors, SSRI was first choice of 75%, an antipsychotic choice of 4%, a mood stabilizing anticonvulsant choice of 6%, and clomipramine 2%. The remaining 13% chose to qualify the response to include 2 first choices. For chorea, an antipsychotic was first choice for 56%, tetrabenazine 15%, amantadine 6%, and benzodiazepines 4%. The remaining 13% chose to qualify the response to include 2 first choices. Drug choice for use as adjunctive therapy was widely variable. Conclusions: Many areas of variability in treatment for irritability, perseverative behaviors, and chorea in HD, have been identified. Results will guide future rounds of the Delphi process to elicit rational causes for differences identified. When complete, this process will clarify useful treatment paradigms that will improve patient care and identify areas in which clinical trials would be most useful.